Applied emblems in Vilnius churches and their literary sources - Gerliakienė, Veronika (Literatūra, 2015)
This article deals with applied emblems found in open Vilnius churches, decorated in the 16th–18th centuries. There are twenty–seven decorative emblems placed on the ceilings and arches of the churches. The verbal part of these emblems, called inscriptio or lemma, is the object of the article.In the 16th century when European literature was enriched with a new genre of emblem, the artists and craftsmen began to use these emblems as a decorative element in their works such as jewelry, armours, carpets, bells, plates, furniture etc. The same phenomenon is seen in the decoration of Vilnius churches.Our research proved that people who worked out the idea of the decoration of the church used two sources for decorative emblems – the Bible (a short quotation from the Bible was used as an inscription) and well-known literary emblems. Speaking about the latter source, some decorative emblems are exact copies of the works of famous 16th century writers, where inscription, icon and concept are taken without any changes. Others show variations on popular literary emblems of that time. Modifications could appear both in verbal and in visual part, thus entirely changing the idea of the emblem.